The Correlation of Vitamin A Deficiency and Micronutrient Consumption in Breast-feeding Moms and the Incidence of ARI and Diarrhea in Babies - Arvina Dian Wahyu Permatasari; Didik Gunawan Tamtomo; Budiyanti Wiboworini (Future Science, 2022)
The incidence of ARI and diarrhea in infants has increased due to the low nutritional content especially vitamin A and other micronutrients in breast milk. This study aimed to determine the relationship between vitamin A deficiency, micronutrient supplement consumption on breastfeeding mothers with ARI (Acute Respiratory Infections) and diarrhea on infant. Cohort study was conducted in four public health center Semarang, Central Java Province from August 2021 to January 2022 Samples were 40 breastfeeding mothers taken by purposive sampling. Data were collected using a questionnaire via Goggle Form to know micronutrient supplement consumption and infant morbidity, and direct interview using 2x24hour food recall questionnaire to know vitamin A deficiency on mothers. Data were analyzed using the spearman rank correlation test. Adequate vitamin A intake was 87.5%, 52.5% mothers consumed micronutrient supplement, 40% infants were suffering from ARI and 32.5% had diarrhea. Relationship between vitamin A deficiency with incidence and frequency of diarrhea was not significant (r =-0.10, p=0.54), (r=-0.07, p=0.63). Relationship between vitamin A deficiency with incidence and frequency of ARI was not significant (r=-0.15, p=0.34), (r=-0.17, p=0.28). Relationship between supplement consumption with incidence and frequency of diarrhea was not significant (r=-0.13, p=0.44), (r=-0.13, p=0.44). Relationship between supplement consumption with incidence and frequency of ARI was not significant r=-0.16, p=0.31), (r=-0.16, p=0.2,9). Thus, vitamin A deficiency and micronutrient supplement consumption was not associated with ARI and diarrhea on infant.